LAYANAN KONSELING DENGAN METODE PEMECAHAN MASALAH UNTUK MENINGKATKAN EFEKTIFITAS DAN EFISIENSI BELAJAR SISWA - Herni Yusnita (Manajer Pendididikan, 2017)
This study aims to find out how to provide counseling services with problem-solving methods in order to improve the effectiveness and efficiency of student learning. The research is a counseling action research conducted in class XII MIA MAN 2 Kota Bengkulu. The data were obtained by using several instruments and techniques of data gathering, namely: interview, questionnaire and observation. In Cycle I, the problem-solving approach through discussion of how to improve the effectiveness and efficiency of learning is still not well implemented. In the discussion the students still have not dared to express an opinion, still does not look good cooperation. In Cycle II, through the guidance of supervising teachers / BK, students carrying out problem solving discussions have done well, besides through the discussion of learning problem solving approach effectively, students can find effective and efficient ways of learning